"We'll See Who's Powerless Now!" Using WALL-E to Teach Administrative Ethics. (30th November 2022) - Zavattaro, Staci M.
Abstract: Using fiction is a popular way to communicate sometimes-complex administrative practices. This paper uses Disney Pixar's WALL-E to examine the movie's ethical dilemmas and how to communicate those in the public management classroom. Through a content analysis of the movie, several overall ethical themes emerged: ethical use of technology, environmental ethics, and consumerism as administrative dilemma. Each is explained using exemplar stories from the film. The research builds on the growing realization that popular culture is relevant to understand governance practices and vice versa.